Designing an Optimal Lightning Protection Scheme for Substations Using Shielding Wires - Khodadadi, A.; Nazari, M. H.; Hosseinian, S. H. (Engineering, Technology & Applied Science Research, 2017)
An optimal lightning protection scheme for a substation using shielding wires is investigated in this paper through computer software analysis. An economic approach is utilized by choosing a reasonable trade-off between protection, the number of shielding wires and the heights of them from the ground. This study is initially applied to a simple two-wire system and then extended to a sample substation. The solution for each problem is executed in MATLAB and 3-D realization is shown.